THE DILEMMA OF TOBACCO AND ILLEGAL CIGARETTES: AN ANALYSIS OF SUPERVISION, OBSTACLES, AND COACHING STRATEGIES IN EAST LOMBOK REGENCY - Rifai Yasin, Abdul Mukmin; Triaji, Bambang (UIN Mataram, 2025)
This study aims to examine the pattern of supervision and obstacles to the circulation of illegal cigarettes in East Lombok Regency. Using a descriptive qualitative method, data was collected through interviews, observations, and documentation studies of Customs officials, local governments, and law enforcement. The results of the study show that the circulation of illegal cigarettes is driven by the surplus of local tobacco production, the high consumption of young smokers, and weak supervision in the distribution channel. The supervisory system implemented both internally and externally still faces structural constraints such as bureaucratic complexity, personnel shortages, and limited operational costs. The Tobacco Products Industrial Estate (KIHT) program is proposed as a coaching approach that can reduce the incentives for business actors to be involved in illegal cigarette production. This study recommends reform of excise supervision policies based on community participation and local economic empowerment as a long-term solution